Qualidade na prestação de serviços públicos: estudo no Campus Cachoeira do Sul/UFSM - Fritz, Gabriela Wioppiold (2021)
This study has as general objective the elaboration of a proposal of actions for the improvement of the quality of the services provided to the students of UFSM/Campus Cachoeira do Sul and, as specific objectives, to identify the activities and processes of attendance to the students in question, to verify the perception of them in relation to the services provided by the Unit Courses Secretariat and by DERCA and, finally, to highlight the critical points that negatively affect the perception of the services provided. For the research, a questionnaire was used with questions elaborated using the SERVPERF and E-S-QUAL scales, adapted to the reality of the study, in addition to questions to identify the profile of the participants. The survey took place during the months of May and July 2020, obtaining responses from a sample of 290 participants. Afterwards, the profile analysis of the participants was carried out and the results obtained through the descriptive and multivariate statistical analyzes were discussed. The results showed as main positive points good presentation, education, helpfulness and knowledge of the employees of the Secretariat of Courses and, for the DERCA website, good organization, the delivery of the requested service and fair time for the service delivery. Regarding the critical points, the research participants highlighted, more significantly, the questions related to the system tangibility and availability, especially in the items “The physical facilities of the Secretariat are visually attractive” and “The DERCA website does not crash”. Considering these aspects, evidenced in the research, proposals for improvements were elaborated, which include adaptation of physical facilities, preparation of tutorials and service protocols, increase of personnel and financial investment.